2002
DOI: 10.1016/s1097-2765(02)00683-4
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of TBP Inhibitors in Global Transcriptional Control

Abstract: The TATA binding protein (TBP) is required for the expression of nearly all genes and is highly regulated both positively and negatively. Here, we use DNA microarrays to explore the genome-wide interplay of several TBP-interacting inhibitors in the yeast Saccharomyces cerevisiae. Our findings suggest the following: The NC2 inhibitor turns down, but not off, highly active genes. Autoinhibition of TBP through dimerization contributes to transcriptional repression, even at repressive subtelomeric regions. The TAN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
99
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(103 citation statements)
references
References 46 publications
2
99
1
1
Order By: Relevance
“…The structure of TBP dimers has been defined crystallographically and through biochemical analysis. Dimer instability caused by mutations along the crystallographic dimer interface correlate with transcriptional derepression in yeast cells (8,15), and this derepression occurs genome-wide at about 7% of all genes (16). Together, these findings indicated that TBP dimerization represents a physiologically important mechanism for auto-inhibiting its DNA binding activity.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…The structure of TBP dimers has been defined crystallographically and through biochemical analysis. Dimer instability caused by mutations along the crystallographic dimer interface correlate with transcriptional derepression in yeast cells (8,15), and this derepression occurs genome-wide at about 7% of all genes (16). Together, these findings indicated that TBP dimerization represents a physiologically important mechanism for auto-inhibiting its DNA binding activity.…”
mentioning
confidence: 88%
“…TBP dimerization adds another level of regulation by also preventing DNA binding through occlusion of the DNA binding surface of TBP. The TAF1 TAND domain and TBP dimerization appear to be partially redundant at a subset of lowly expressed genes in the yeast genome (16). Mot1 and another TBP inhibitor NC2 might work in concert to disassemble TBP from an otherwise active transcription complex (28) and thus are typically associated with active genes (16).…”
Section: Fig 6 Suppression Of Toxicity Associated With Tbp(n69r)mentioning
confidence: 99%
“…Oxygen deficiency induces binding of NC2 to certain mammalian genes correlated to repression of transcription, which argues for a similar role in vivo (37). However, in Saccharomyces cerevisiae, NC2 seems to affect gene transcription both positively and negatively (38,39). Chromatin immunoprecipitation (ChIP) data suggested that the cofactor localizes to both inactive and active genes.…”
mentioning
confidence: 99%
“…Inasmuch as TBP has a relatively high affinity for nonspecific DNA (46) and in this capacity can assemble pol II transcription complexes, the cell is likely to employ a number of mechanisms to prevent this nonproductive and potentially detrimental assembly. Our previous studies (26,30,37,39,40) suggest that TBP dimerization represents a physiologically important auto-inhibitory mechanism by which unregulated binding of TBP to DNA is prevented. If so, then there are likely to be mechanisms that dissociate TBP dimers as a prelude to productive binding.…”
Section: Discussionmentioning
confidence: 99%
“…Note that the TBP and SNR6 derivatives are present in a wild type TBP and SNR6 background. Null TBP is a ϩ1 frameshift (40). B, quantitation of 12 replicates of data presented in A in which the median ratio of snr6(⌬BB)/ ⌿-WT, normalized to null TBP, is graphed.…”
Section: Fig 6 Effect Of Tbp Mutants On Pol III Transcriptionmentioning
confidence: 99%